THE USE OF EUPHEMISM IN TOBA BATAK MOVIES - Dimpan Silaban; Ignesia Sundari; Desmalia Purba (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This research deals with The Use of Euphemism in Toba Batak Movies. This research is conducted to find out the types, styles and functions of euphemism in Batak movies. The descriptive qualitative method is the research design of this study. The data were collected from Batak movies through the process of watching the movies, transcribing the data and selecting the euphemistic words or phrases which were relevant to be the data. As the result, the research found: there were four types of euphemism, they were metaphor, general for specific, idiom, and hyperbole; there were three styles of euphemism: casual, consultative, and frozen; and there were three functions of euphemism: evaluate, informs, and formal.